Recuperação e proteção de uma nascente da Microbacia do Urumari no município de Santarém - PA utilizando o modelo "Caxambu" - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2018)
The Disordered urban sprawl, especially in areas called APPs (Permanent Preservation Areas) and, consequently, the removal of riparian forest and the sedimentation of the water body, animal trampling, people’s traffic due the proximity of roads, has been causing several environmental impacts that compromise the physical integrity of the Urumari microbasin. This study aimed to implanting the Caxambu Model Source Protection System for the recovery and preservation of the Water Source located near the Urumari microbasin. This technology was developed by Epagri (Company of Agricultural Research and Rural Extension of Santa Catarina) in the early 90's and applied in the city of Caxambu do Sul, has a great environmental advantage, the system ensures that the source is not contaminated by external agents, it’s a simple, practical, efficient and low-cost system that ensures the correctly performs of water quality. Therefore, it’s possible to affirm that this method is efficient and extremely important to minimize the problems of quantity and quality of water available in rural or urban areas. According to the survey, both springs and riparian forests need to be protected, within a radius of 50 meters to the springs and 30 meters to the riparian forests at both edges of the stream. Together with this, the procedure the area needs to be surrounded to avoid deforestation, the compaction of the soil and the reduction of the flow of the water body, protected by the "Caxambu" system. The water of this spring meets the standards of surface water quality, Article 4 Special Class, as established by Resolution No. 357 of March 17, 2005, National Environmental Council - CONAMA.
Keywords: Nascentes; Mata Ciliar; Fonte Caxambu; CNPQ:: ENGENHARIAS